Dothidea kunmingensis, a novel asexual species of Dothideaceae on Jasminum nudiflorum (winter jasmine) from Southwestern China - Gao, Ying; Monkai, Jutamart; Gentekaki, Eleni; Ren, Guang-Cong; Wanasinghe, Dhanushka N.; Xu, Jian-Chu; Gui, Heng (Phytotaxa, 2021)
During a survey of saprobic microfungi in Southwest China, a coelomycetous fungus was found on dead twigs of Jasminum nudiflorum in Kunming, Yunnan Province. Based on a detailed morphological characterization coupled with multi-locus phylogenetic analyses, the fungus was identified as a new species in the genus Dothidea. Phylogenetic analyses using a combined matrix consisting of internal transcribed spacer (ITS), large subunit rRNA (LSU), small subunit rRNA (SSU), beta tubulin (tub2) and translation elongation factor-1 alpha (tef1-α) confirmed its placement in Dothideaceae and revealed a sister relationship to Dothidea eucalypti. The new species is characterized by pycnidial conidiomata, ampulliform or doliiform conidiogenous cells as well as aseptate, subglobose to ovoid, hyaline to pale-brown conidia. Comprehensive descriptions and illustrations are provided. Morphological characteristics of asexual morph taxa in Dothideaceae are also summarized and discussed.